Discriminatory Indices of Typing Methods for Epidemiologic Analysis of Contemporary Staphylococcus aureus Strains. Issue 37 (September 2015) - Rodriguez, Marcela; Hogan, Patrick G.; Satola, Sarah W.; Crispell, Emily; Wylie, Todd; Gao, Hongyu; Sodergren, Erica; Weinstock, George M.; Burnham, Carey-Ann D.; Fritz, Stephanie A.
Abstract : Abstract: Historically, a number of typing methods have been evaluated for Staphylococcus aureus strain characterization. The emergence of contemporary strains of community-associated S. aureus, and the ensuing epidemic with a predominant strain type (USA300), necessitates re-evaluation of the discriminatory power of these typing methods for discerning molecular epidemiology and transmission dynamics, essential to investigations of hospital and community outbreaks. We compared the discriminatory index of 5 typing methods for contemporary S. aureus strain characterization. Children presenting to St. Louis Children's Hospital and community pediatric practices in St. Louis, Missouri (MO), with community-associated S. aureus infections were enrolled. Repetitive sequence-based PCR (repPCR), pulsed-field gel electrophoresis (PFGE), multilocus sequence typing (MLST), staphylococcal protein A ( spa ), and staphylococcal cassette chromosome (SCC) mec typing were performed on 200 S. aureus isolates. The discriminatory index of each method was calculated using the standard formula for this metric, where a value of 1 is highly discriminatory and a value of 0 is not discriminatory. Overall, we identified 26 distinct strain types by repPCR, 17 strain types by PFGE, 30 strain types by MLST, 68 strain types by spa typing, and 5 strain types by SCC mec typing. RepPCR had the highest discriminatory index ( D) of all methods ( D  = 0.88), followed by spa typing ( D  = 0.87), MLST ( D  = 0.84), PFGE ( D  = 0.76), and SCC mec typing ( D  = 0.60). The method with the highest D among MRSA isolates was repPCR ( D  = 0.64) followed by spa typing ( D  = 0.45) and MLST ( D  = 0.44). The method with the highest D among MSSA isolates was spa typing ( D  = 0.98), followed by MLST ( D  = 0.93), repPCR ( D  = 0.92), and PFGE ( D  = 0.89). Among isolates designated USA300 by PFGE, repPCR was most discriminatory, with 10 distinct strain types identified ( D  = 0.63). We identified 45 MRSA isolates which were classified as identical by PFGE, MLST, spa typing, and SCC mec typing (USA300, ST8, t008, SCC mec IV, respectively); within this collection, there were 5 distinct strain types identified by repPCR. The typing methods yielded comparable discriminatory power for S. aureus characterization overall; when discriminating among USA300 isolates, repPCR retained the highest discriminatory power. This property is advantageous for investigations conducted in the era of contemporary S. aureus infections.